A study to assess the unmet medical needs associated with the use of basal insulin in patients with type 2 diabetes - Frechtel, Gustavo Daniel (2021)
Aim: To describe in a real-world setting, the proportion of patients with a symptomatic hypoglycaemic event and the proportion of individuals with type 2 diabetes, who newly or recently initiated with basal insulin, achieving individual or general HbA1c target. Materials and Method: DINAS-AR was a national prospective observational study to assess the unmet needs in patients with type 2 diabetes treated with basal insulin with or without oral antihyperglycaemic drugs and/or GLP-1 receptor agonist. The study was conducted at 19 hospitals. Results: A total of 385 uncontrolled patients (≥18 years) who recently initiated basal insulin or who initiated treatment within a year prior to study enrolment entered the study. Outcomes were follow-up incidence of hypoglycaemic events, change of HbA1C and achievement of HBA1c <7% or individual target. A total of 44 patients (11.9%) reported the occurrence of ≥1 symptomatic hypoglycaemia event(s). HbA1c reductions were greater in patients who had recently initiated treatment with basal insulin (between 15 and 90 days prior to study entry) vs patients who initiated treatment within 1 year. A total of 80 patients (31.6%) achieved individual HbA1c target (or target <7.0%) at Week 24. Furthermore, the proportion of patients achieving this target without symptomatic hypoglycaemia was 26.1% (n = 66). A lower percentage of glycemia target achievement was observed in patients reporting hypoglycaemia (n = 14), 20.6% of all patients reporting hypoglycaemia event(s) vs (n = 66) 35.7% of all patients without hypoglycaemia event reported. Conclusion: In this real-world study, although the hypoglycaemia rate was not high in adults with type 2 diabetes treated with insulin, there was a lower percentage of patients that achieved glycemic target among those reporting hypoglycaemia events vs patients who did not report them.